Pengaruh Integrasi Pelabuhan PT. Berlian Manyar Sejahtera dengan Kawasan Industri JIIPE terhadap Efisiensi Distribusi Logistik - Alfiana Noor Fajari; Faris Nofandi; Vigih Hery Kristanto; Indah Ayu Johanda Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of port integration of PT Berlian Manyar Sejahtera with JIIPE Industrial Estate on logistics distribution efficiency. The background is the existence of distribution costs in Indonesia, which are relatively expensive. The integration of ports with industrial estates and other factors could cut distribution costs. The purpose of this research is to find out how many percent of the influence of proximity distance for distribution costs and also the time in the distribution process. In this research, a quantitative methods is used which is assisted by a software, namely SPSS version 27. Data collection techniques were carried out by interviews, documentation, and literature study. The data used includes the distance from the port to the warehouse receiving goods, distribution rates, and the length of time in the loading and unloading process. The results of the analysis show that there is an influence between distance, costs, and tariffs in the distribution process. And how this integration is significantly beneficial for service users